FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA KUNJUNGAN POLIKLINIK GIGI DI PUSKESMAS KARANGANYAR II DEMAK - Pamunarsih Pamunarsih; Bedjo Santoso; Sukini Sukini (Jurnal Kesehatan Gigi, 2018)
TITLEFACTORS AFFECTING THE LOW UTILIZATION OF DENTAL POLYCLINIC IN KARANGANYAR II  COMMUNITY HEALTH CENTER ON DEMAKABSTRACT One of the efforts to maintain the teeth is by maintaining dental health, routine control of dental or dental checkup through healthcare facilities. High caries prevalence rates are not matched by utilization of existing dental facilities. The average daily visit of dental polyclinic is 75 people, it is considered less than 4% of the population in Health center of Karanganyar II, which is 146 people. The purpose of this study is to find out the factors that influence the low utilization of dental poly of the Karanganyar II Health Center in Demak Regency.Analytic research type using the cross-sectional method. Respondents were patients who came to Dental Poly Karanganyar II Demak in 2017 of 96 patients taken by accidental sampling technique. Data collection tool is a questionnaire, while analysis of the data itself is done by univariate and bivariate, to answer the hypothesis used Chi-Square test.There is an influence of knowledge level with the utilization of dental poly in Health center of Karanganyar II Demak (p-value = 0,000). There is an influence of respondent attitude with the utilization of dental poly in Health center of Karanganyar II Demak (p-value = 0,000). There is no effect of infrastructure on the utilization of dental poly in Health center of Karanganyar II Demak (p-value = 0,107). There is an influence of health officer attitude with a utilization of dental poly in Health center of Karanganyar II Demak (p-value = 0,000). There is an influence of knowledge level, respondent attitude, means of infrastructure, and attitude of health officer to low utilization of dental poly in Health center of Karanganyar II Demak. Keywords : Utilization, Dental Poly, Health center